Synthesis and characterization of size-selective nanoporous polymeric adsorbents for blood purification. - Malik, Danish Javed; Webb, C.; Holdich, Richard G.; Ramsden, Jeremy J.; Warwick, Graham L.; Roche, I.; Williams, David John; Trochimczuk, Andrzej W.; Dale, James A.; Hoenich, Nicholas Andrew (Elsevier, 2009)
Crosslinked polystyrene co-divinylbenzene adsorbent microspheres with median diameters between 40 and 300 μm, with an enhanced proportion of mesopores in the range 4–10 nm, have been synthesized using a membrane emulsification technique. The aim was to develop an adsorbent for the selective removal of middle molecular weight uraemic toxins (size range 0.5–20 kDa), e.g. β2-microglobulin (11.8 kDa), whilst size-excluding larger blood proteins, e.g. serum albumin (MW 69 kDa). Using inverse size exclusion chromatography, the role of size exclusion has been demonstrated using hen egg lysozyme (a surrogate for β2-microglobulin) and human serum albumin as model proteins for batch adsorption studies. The adsorbent sample possessing a nanoporous structure with pores predominantly smaller than 10 nm successfully size-excludes serum albumin whilst displaying significant adsorption capacity for the middle molecular weight lysozyme (14.3 kDa).
Keywords: Middle molecular weight toxins; Haemoadsorption; Inverse size exclusion chromatography; Haemodialysis; Microspheres; Membrane emulsification